Impact of Substrate Hydrophobicity on Layer Composition and Work Function of PEDOT:PSS Thin Films. Issue 1 (19th October 2021) - Wu, Di; Wan, Shanshan; Zhai, Tianshu; Yang, Jiacheng; Wang, Rongbin; Duhm, Steffen
Abstract : Ultraviolet and X‐ray photoelectron spectroscopy (UPS and XPS) are used to investigate the impact of surface hydrophobicity on the work function of spin‐coated poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) thin films. Although O2 –plasma or UV–ozone treatment of indium tin oxide (ITO) changes the substrate hydrophobicity, the work functions of subsequently spin‐coated PEDOT:PSS layers are not affected and stay constant at around 5 eV. ITO modification by a self‐assembled monolayer of p ‐(trifluoromethyl)phenylphosphonic acid leads to a pronounced contact angle of 90°, resulting in a PSS‐rich PEDOT:PSS surface (as shown by XPS) and a work function of 5.15 eV (as shown by ultraviolet photoelectron spectroscopy). This can be rationalized by an increased bulk chemical potential of PEDOT:PSS. Abstract : The work function of spin‐coated PEDOT:PSS thin films on O2 –plasma‐ or UV–ozone‐treated indium tin oxide is around 5 eV and rather independent of the substrate cleaning parameters. Moreover, the PEDOT:PSS layer thickness does not affect the work function. Increasing the substrate hydrophobicity by self‐assembled monolayers provides a facile way to increase the PEDOT:PSS work function up to 5.15 eV.